Mutual impedance with finite feed gap model of dipole antennas using the induced EMF method - Abdul Malek, Norun Farihah; Jusoh, Ahmad Zamani; Badron, Khairayu; Ismail, Ahmad Fadzil (Institute of Electrical and Electronics Engineers Inc., 2016)
Mutual coupling in antenna arrays bring a significant impact especially when antenna elements are placed close with each other. It affects antenna performance, communication capacity and so on. Likewise, an accurate analysis of mutual coupling which can be expressed in terms of mutual impedance is important. A few analytic approaches for mutual impedance between two dipoles are available, one of it is the Induced EMF method. The Induced EMF method is accurate for short and thin, with an infinitesimal feed gap,which is impractical. A finite feed gap which is practical, can be modeled using electromagnetic simulation approaches. However, no analytical techniques are available to compare the results of the design with numerical software. The finite feed gap modelling of the mutual impedance using the Induced EMF method will be highlighted in this paper. The results are compared with other electromagnetic software. Then, the effect of the finite feed gap model has been observed in the far field pattern of dipole antenna arrays and they are in good agreement with other electromagnetic software.